2005
DOI: 10.1097/01.wnr.0000187630.45633.0a
|View full text |Cite
|
Sign up to set email alerts
|

Lack of standard N2 in elderly participants indicates inhibitory processing deficit

Abstract: We analyzed the cortical responses to standard stimuli presented in an auditory oddball paradigm from two groups of young and elderly participants in unattended and attended conditions. A sustained negativity (N2) followed N1 and P2 in the responses of the young participants. This negativity was reduced or absent in the elderly. With attention, the early portion of N2 (N2early) decreased in both groups, whereas the late portion (N2late) increased only in young participants. We suggest inhibitory processes at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 24 publications
4
23
0
1
Order By: Relevance
“…The N2 component is responsible for the classification or categorization of deviant stimuli (Mueller et al 2008), a previous and required process before storing in working memory. Most studies showed a decrease in the N2 amplitude and latency from childhood to adulthood (Ladish and Polich 1989;Iragui et al 1993;Lembreghts et al 1995;Johnstone et al 1996;Bertoli and Probst 2005;Mueller et al 2008;Č eponien_ e et al 2008;Tsai et al 2012), our results are consistent with literature at Fz and Cz but only a slight decrement in latency until 40 years old (Figs. 5, 6).…”
supporting
confidence: 82%
“…The N2 component is responsible for the classification or categorization of deviant stimuli (Mueller et al 2008), a previous and required process before storing in working memory. Most studies showed a decrease in the N2 amplitude and latency from childhood to adulthood (Ladish and Polich 1989;Iragui et al 1993;Lembreghts et al 1995;Johnstone et al 1996;Bertoli and Probst 2005;Mueller et al 2008;Č eponien_ e et al 2008;Tsai et al 2012), our results are consistent with literature at Fz and Cz but only a slight decrement in latency until 40 years old (Figs. 5, 6).…”
supporting
confidence: 82%
“…These subcomponents appear between 200 and 350 ms, and their topography, neural sources, and proposed function varies depending on subtype (Folstein and Van Petten, 2008). We focussed on the standard N2, typically observed in response to stimuli that involves inhibitory processing, for example, ignoring the standard stimulus in an oddball task (Bertoli and Probst, 2005). It has a fronto-central distribution with neural sources in the right orbito-frontal cortex and anterior cingulate (Falkenstein, 2006, Näätänen and Picton, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, P3 habituation may be less pronounced in more anterior regions. Since N2 is thought to be involved in inhibition of irrelevant information processing (Bertoli and Probst, 2005), it is reasonable to expect that N2 and P3 amplitudes will be inversely related.…”
Section: Discussionmentioning
confidence: 99%
“…P2 is related to stimulus classification and it also reflects auditory driven output of the mesencephalic reticular activating system (Crowley and Colrain, 2004). N2 is thought to be related to advanced processes of stimulus evaluation, as conflict detection and stimulus classification, and to the regulation of long-term changes in information processing, and it is probably modulated by temporal attention (Kinoshita et al, 1996;Bertoli and Probst, 2005;Correa et al, 2006;Umbricht et al, 2006). The amplitude of P3 reflects brain processes related to decision making, depth of processing and memory as well as the probability of the stimulus and the relevance to the subject (Johnson, 1986;Pelosi and Blumhardt, 1999;Wickens et al, 1983;Donchin and Coles, 1988).…”
Section: Introductionmentioning
confidence: 99%